Appraisal of the preparedness of ECOWAS towards a common currency - Louis Sevitenyi Nkwatoh (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
This study appraised the preparedness of Economic Community of West African States (ECOWAS) towards the adoption of a common currency by analysing the degree of symmetry and sizes of identified shocks across member countries. The analysis was situated within the framework of the Optimum Currency Area (OCA) theory and the structural vector autoregressive (SVAR) model was employed on secondary data from 1975 to 2015. The findings reveal that external supply shocks across ECOWAS countries are symmetric except for Sierra Leone, while demand, supply and monetary shocks among member countries are asymmetric. The absolute relative sizes of the different shocks across member countries are high and different in sizes. This implies that ECOWAS countries are not fully prepared to adopt a common currency and the fixed exchange rate as a stabilization policy for the entire West Africa. Hence ECOWAS governments should further shift the targeted date beyond 2020 to create ample time for member countries to get fully prepared.